Análisis de la Incidencia del Populismo Punitivo en la Política Criminal Colombiana (2023)
This study arises with the central purpose of promoting education and understanding in people about the need for an adequate and effective criminal policy, exposing in turn how harmful, inefficient, and obsolete are the measures and projects carried out by social pressure or for political purposes, this taking into account the current situations in Colombia and the world. In this sense, it is intended to show from an academic and legal framework how the anomaly of punitive populism is projected and materializes, understood as a phenomenon that consists in the legislation and implementation of penalties that are usually popular among society, such as exaggerated penalties, penalties that go against the academic and legal foundations, guiding principles of criminal law and the purpose of the penalty in our legal system. The methodological approach comprises a non-experimental, transectional descriptive quantitative design supported by a documentary research phase of specialized articles, normative references, and primary and secondary sources, as support for the design and application of a perceptual survey on aspects associated with the incidence of punitive populism in the Colombian criminal policy. From the analysis of the results, it is evident that penalties in Colombia are not, nor should they be seen or exposed as punishment, but rather as a process of redemption and transition. Additionally, it must be considered that high or capital sentences do not generate a reduction in crime, but even so this phenomenon continues to occur both in our country and in others, this under the assumption of generating a “solution” for the problems of security and crime. Consequently, the true intention is not such a benevolent goal, the true objective only responds to political strategies, a situation that does not allow socio-legal progress at present.